Answers

The Brainliest Answer!
2016-05-08T05:56:46+05:30
a) | x 2 | = x 2

b) | x | 2 = x 2

c) | | x | | = | x | 

d) | x 2 + 4 | = x 2 + 4 

e) | -x 4 - 9 | = x 4 + 9 

f) | -| x | - 2 | = | x | + 2 

g) | -x / 3 | = | x | / 3 

h) | -x 2 - y 2 + 2xy| = | -(x 2 + y 2 - 2xy) | = | -(x - y) 2 | = (x - y) 2
1 5 1
2016-05-13T13:02:32+05:30
Simplify the following absolute value expressions a) | x ²| = x²
b) | x |² = x²
c) | | x | | = x
d) | x² + 4 | = x² + 4
e) | -x⁴ - 9 | = x⁴ + 9
f) | -| x | - 2 | = x + 2
g) | -x / 3 | = x/3
h) | -x² - y² + 2xy| = x² + y² - 2xy = (x -y)²
0